Sustainability Report and Company Performance: The Geopolitical Impact in Indonesia - Rahayu, Sri; Ekawanti, Wahyumi; Utomo, Mohamad Nur; Nainggolan, Yohanna Thresia; Jalolov, Otabek (Universitas Brawijaya, Indonesia, 2024)
Recent global crises, such as the 2022 Russia-Ukraine conflict and heightened global temperatures, have emphasized the need for robust sustainability practices amid volatile geopolitical environments. This research aims to analyze the impact of geopolitical risks on companies that publish sustainability reports in relation to company performance as measured by firm value. The research sample includes 19 food and beverage companies, observed over five years (2018–2022). Data analysis is conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with WarpPLS version 8.0, a robust tool for assessing complex relationships in small to medium-sized samples. The findings reveal that sustainability report disclosure positively influences firm value. However, this positive effect is significantly reduced in the presence of geopolitical risks, highlighting the vulnerability of firm performance to external political factors, even when sustainable practices are prioritized. The role of geopolitics as a moderating variable in the relationship between sustainability reports and company value is complex and crucial in the current global business context, unlike previous research that used geopolitics as an independent variable. This result underscores the importance of proactive risk management strategies to mitigate the impact of geopolitical tensions on sustainability efforts. By highlighting the moderating role of geopolitics, this study contributes to a deeper understanding of how external risks can influence the effectiveness of sustainability efforts on firm value in emerging markets.